Stages and the temporal variation of Eurygerris fuscinervis (Heteroptera: Gerridae) in the Andes of Colombia - PADILLA-GIL, DORA N.; ARCOS-P., OSVALDO (Revista Colombiana de Entomología, 2010)
The stages of post-embryonic development of Eurygerris fuscinervis are described and illustrated. The number of individuals per stage and the temporal variation, during the dry and rainy seasons, were studied in six localities located in four municipalities of the Department of Nariño, Colombia: Pasto, Buesaco, Funes y Tangua. A total of 1,342 individuals were collected, 831 adults and 511 nymphs, corresponding to five stages. The populations exhibited temporal stability; there were no significant differences with respect to the dry and rainy seasons, nor with respect to altitude (2,260−2,700 m).